Similarities and differences in the dental tissue proportions of the deciduous and permanent canines of Early and Middle Pleistocene human populations. Issue 2 (5th October 2021) - García‐Campos, Cecilia; Modesto‐Mata, Mario; Martinón‐Torres, María; Martín‐Francés, Laura; Martínez de Pinillos, Marina; Arsuaga, Juan Luis; Bermúdez de Castro, José María
Abstract: The two‐ and three‐dimensional assessment of dental tissues has become routine in human taxonomic studies throughout the years. Nonetheless, most of our knowledge of the variability of the enamel and dentine dimensions of the human evolutionary lineage comes from the study of permanent dentition, and particularly from molars. This leads to a biased view of the variability of these features. Due to their early formation and rapid development, the deciduous teeth allow more simplified inferences regarding the processes involved in the dental tissue development of each group. Therefore, their study could be very valuable in dental palaeohistology. In this research, we have explored the dental tissue proportions of the deciduous canines belonging to some human samples of the Early and Middle Pleistocene. The purpose of this was to discuss the meaning of the similarities and differences observed in their histological pattern, as well as to evaluate the degree of covariance with that observed in the permanent dentition of these populations. Our results show that, although there are some similarities in the dental tissue proportions between the deciduous and permanent canines of the study samples, the two dental classes do not provide a similar or comparable pictures of the dental tissue pattern present in the dentition of fossil hominins. Future works on the dental tissue patterns of the anterior and posterior dentition, including deciduous teeth, of fossil samples, may help to shed light on this hypothesis. Abstract : Deciduous teeth allow more simplified inferences regarding the processes involved in dental tissue development, therefore, they are very valuable in dental palaeohistology. In this research, we have explored the dental tissue proportions of the deciduous canines belonging to some human samples of the Early and Middle Pleistocene. Our results show that deciduous and permanent canines do not provide a similar picture of the dental tissue pattern present in the dentition of fossil hominins.